Problems of binational marriages. Analysis of Internet discussion forums - Biedroń, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Strong homogenous tendencies with regard to such criteria as the nationality, the ethnic race/group, or the practised religion in the Polish culture are typical of the strategy of the selection of the spouse. Data from the Central Statistical Office indicates that the percentage of bicultural marriages isn’t high and is fluctuating (in different years) up to a maximum of 2%. Potentially partners from different countries and cultures may differ in a whole spectrum of issues ranging from the fundamentals associated with the professed worldview and axiological system to the, seemingly trivial, everyday preferences. Analysis of statements of the participants of discussion boards devoted to the functioning of this type of partnership, and the official website of the Association of Poles in Marriages with Foreigners, provided a response to the question: what problems are facing this kind of couples, which they believe poses the greatest obstacle to the successful functioning of the relationship?
Keywords: binational marriage; mixed marriages; biculturalism; family; conflicts